2019
DOI: 10.15644/asc53/3/1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effectiveness of Occlusal Splint Therapy Compared to Placebo in Patients with Chronic Temporomandibular Disorders

Abstract: PurposeThe aim of this study was to compare long-term effectiveness of stabilization splint (SS) with that of placebo splint (PS) in chronic TMD patients and to investigate differences in treatment outcomes based on diagnostic subgroups [disc displacement (DD)/myofascial pain (MP)].Materials and MethodsThirty-four female participants, diagnosed with chronic TMD, were classified in groups: one provided with SS and other with PS and were followed for six months. Treatment outcomes included spontaneous pain [visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 23 publications
1
14
0
2
Order By: Relevance
“…As a consequence, symptoms such as: bruxism, pain in the temporomandibular joints (TMJs), and headaches may appear. Long-term symptoms of SSDs may contribute to irreversible changes in this system, resulting in impaired chewing, swallowing, speech, and breathing functions [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Additionally, long-term reports about TMJ internal derangements were released [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, symptoms such as: bruxism, pain in the temporomandibular joints (TMJs), and headaches may appear. Long-term symptoms of SSDs may contribute to irreversible changes in this system, resulting in impaired chewing, swallowing, speech, and breathing functions [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Additionally, long-term reports about TMJ internal derangements were released [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In medical terms, it is defined as a disorder of the body's homeostasis caused by physical or psychological elements [6][7][8]. It can be caused by mental, physiological, anatomical [7,8], or physical factors [9][10][11]14]. Stressful situations lead to increased muscle tension, which is the body's natural response to threat.…”
Section: Introductionmentioning
confidence: 99%
“…Yatani et al [19] and Vrbanovic & Alajbeg [66] reported long-term stability of TMD treatment using occlusal splints. This type of data was not found in the literature for the results of JFO, showing the need for research about the stability of JFO results.…”
Section: Discussionmentioning
confidence: 99%
“…5 One study found that relative to a placebo group, a group treated with splint could more easily open the mouth without pain and showed a practical treatment effect after 6 months. 20 However, some side effects can occur including occlusal changes, dental/myofascial discomfort, TMJ pain, xerostomia, and excess salivation. The occlusal changes can be significant.…”
Section: Discussionmentioning
confidence: 99%